POTENSI NILAI MANFAAT EKONOMI DAN KESEDIAAN PETANI MEMBAYAR JASA LAYANAN IRIGASI CIPANGARANGAN - Bintang Maulana Gentzora; Trisna Insan Noor; Eka Purna Yudha (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
This research is motivated by the inequality of availability with the needs of Cipangarangan irrigation water. Farmers using water are proposing to revitalize the irrigation. Based on this background, the objectives of this study are a) to estimate the value of economic benefits from irrigation revitalization; b) analysis of ability (ATP) and willingness to pay WTP) of farmers for irrigation services, and c) knowing ATP and WTP of irrigation services with farmer characteristics. The method used is a mixed method research with primary and secondary data. Respondents were determined using proportional random sampling. The conclusions of the research results: a) Cipangarangan irrigation revitalization is predicted to increase the economic benefit value of Rp. 10,934,091,000 / year, originating from an increase in the net value of rice farming income of Rp. 7,707,231,000 and labor absorption equivalent to Rp. 3,226,860,000 / year. b) The average ATP for irrigation services is relatively smaller (Rp. 38,749) when compared to the average WTP (Rp. 71,195). This condition shows that the range of farmers' ability to pay for irrigation services is smaller than their willingness to pay (ATP <WTP). Conditions like this illustrate the courage of farmers to pay for irrigation services beyond their reach, the utility of irrigation services is relatively higher than the income of service users. This condition is called Captive riders.